Implementation of the New Public Service Principle as a Basis for Incremental Reform Action in the Dana Indonesiana Program - Darmawati, Darmawati; Intan Suciati Daeng Baji; Sa’adati Sa’adati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study analyzes the Dana Indonesiana cultural endowment fund (DAKB) program as a form of incremental service reform using the principles of New Public Service (NPS). The background of this study was triggered by the imbalance in the realization of the utilization of the cultural endowment fund compared to the results of management, which is 60% of IDR 337.5 billion. Not to mention when associated with the impact of funding on the cultural economy which from the realization of its utilization alone is not optimal. So logically, the impact of the cultural economy on improving the welfare of cultural actors is certainly not optimal. However, the objectives and benefits of the study are emphasized on enriching knowledge of the principles of New Public Service, and focus on indicators of inclusivity, transparency, and community involvement. This study was designed using a qualitative explanatory method, with data collection techniques through interviews and literature analysis. The study succeeded in explaining that the Dana Indonesiana DAKB service adheres to an incremental bureaucratic reform model. It is recorded that policy reform, service inclusivity is already very good at above 80%. Research shows that Dana Indonesiana has an important role in democratizing access to cultural resources, encouraging collaborative governance, and positioning the government as a servant, serving and not controlling. The indicators of collaborative work, community-based, and accountability are quite high. The weakness is not in the service providers, but lies in the beneficiaries who have minimal effort and are less responsive. Therefore, new policy innovations are needed so that Dana Indonesiana services have an impact on the cultural economy, and the coverage area becomes wider.